Voice pattern analysis using imaging technique - Wan Sulaiman, Wan Suzaimi (2003)
Everyone has their own spectrum of voice and we can see the differences through the spectrum. There are many ways to analyse the voice pattern. In this thesis the voice pattern was analysed using imaging technique. In this project, the voice obtained from a person and recorded for the experiment.